The lived experience of patients with obesity: A systematic review and qualitative synthesis. (16th August 2021) - Farrell, Emma; Hollmann, Eva; le Roux, Carel W.; Bustillo, Marta; Nadglowski, Joe; McGillicuddy, Deirdre
Summary: Although the deleterious effects of obesity have been well documented in terms of morbidity and mortality, less is known about what it is like to live with this complex and chronic disease. This study systematically reviewed and synthesized peer‐reviewed studies relating to the lived experience of patients with obesity. A total of 12, 388 records were screened, resulting in the inclusion of 32 final studies. Meta‐ethnographic synthesis of these 32 studies generated five "third‐order constructs" or themes: the development of obesity; a life limited; stigma, judgment, shame, and blame; treatment and; experiences of specific or minority groups. These constructs describe, from the patient's perspective, the factors associated with the development and maintenance of obesity; the effects of the disease on their day‐to‐day lives; the impact of the stigma and judgment many patients are subjected to; and their experience of accessing, or trying to access, treatment for their healthcare needs. This synthesis reveals the dearth of studies that focus solely on the experience of the patient and highlights the tendency for participant‐informed, rather than participatory, methods in obesity research. It concludes with a call for further participatory research into the experiences of people living with obesity.